Heavy Metals (Zn, Cu, Pb, Cd and Hg) Contents and Fatty Acids Ratios in Two Fish Species (Scomberomorus commerson and Otolithes ruber) of the Persian Gulf: Heavy metals contents of fish from the Persian Gulf - Mohammad Javad Khoshnoud; Keivan Mobini; Katayoun Javidnia; Parisa Hosseinkhezri; Khosro Aeen Jamshid (Iranian Journal of Pharmaceutical Sciences, 2011)
This study was conducted to determine the concentrations of metals (Zn, Cu, Pb, Cd and Hg) in two commercial fish species of the Persian Gulf (coast of Bushehr Province in Iran), as well as in the sea waters. The concentrations of metals were determined by using differential pulse anodic stripping voltammetry (DPASV). Two selected species were narrow-barred Spanish mackerel and tiger tooth croaker. The same fish were also used to determine the ratios of fatty acids including saturated fatty acids (SFA), monounsaturated fatty acids (MUFA), and polyunsaturated fatty acids (PUFA). Fish and water samples were collected from three different areas, namely Bushehr (station 1), Tangestan (station 2) and Dayyer (station 3). Results showed that all metals contents had lower concentration of the mean values than the permissible limits set by FAO/WHO. It can be concluded that both fish species studied are safe to be consumed. In the present study, for the first time correlation of metals concentrations with fatty acids ratios in both species was statistically analyzed and showed no correlation except for Pb mean value which had negative correlation with PUFA% in tiger tooth croaker species.